Phytochemicals, Antioxidant, and Chemopreventive Potential of Tamarix Indica Leaf Extracts. Issue 2 (3rd April 2022) - Paul, Susmita; Naher, Kamrun; Yeasmin, Sanzida; Acharrya, Rabindra Nath; Golder, Mimi; Ahmed, Khondoker Shahin; Hossain, Hemayet; Dev, Shrabanti; Das, Asish Kumar
ABSTRACT: Ethanolic leaf extract of Tamarix indica was evaluated for the antioxidant and anticancer activities and toxicological profiles. The flavonoid, phenolic, and tannin contents of leaves were estimated as 5.3068 mg of QE g −1, 8.786 mg of GAE g −1, and 8.5216 mg of GAE g −1, respectively. In DPPH scavenging assay, T. indica leaves' extract had an IC50 value of 74.38 μg mL −1 . HPLC-DAD analysis identified catechin hydrate, vanillic acid, rutin hydrate, p -coumaric acid, and myricetin in different concentrations. In brine shrimp lethality bioassay, the IC50 value of the extract was 19.928 µg mL −1 . Chemopreventive activity was evaluated using DMBA/croton oil-induced skin cancinogenic model mice. Oral treatment of the extract at different doses reduced the size, number, yield, and burden of tumor in skin carcinogenic mice. Natural antioxidants GSH and SOD increased with extract treatment. Additionally, reduction in blood bilirubin, SGPT, and SGOT levels were observed in extract treated mice. In acute toxicity study, no mortality was observed in mice justifying the safety of the extract.